If the equation is y = 3(x + 4)2<span> - 6, the value of h is -4, and k is -6. To convert a quadratic from y = ax</span>2<span> + bx + c </span>form to vertex form, y = a(x - h)2+ k, you use the process of completing the square. Let's see an example. Convert y = 2x2<span> - 4x + 5 into </span>vertex form<span>, and state the </span>vertex<span>.</span>
Answer:
I think its b
Step-by-step explanation:
A=2πrh+2πr2=2·π·5·12+2·π·52≈534
Answer:
Complementary
Step-by-step explanation:
Complementary Angles add up to 90°
Supplementary Angles add up to 180°
60 + 30 = 90
Are we solving for x or y?